The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/5621341
|View full text |Cite|
|
Sign up to set email alerts
|

The Impact of Catalpol on Proliferation, Apoptosis, Migration, and Oxidative Stress of Lung Cancer Cells Based on Nrf2/ARE Signaling

Abstract: The effects of catalpol on lung cancer cell proliferation, apoptosis, migration, and oxidative stress via the Nrf2/ARE signaling pathway are investigated in this work. Catalpol-12 g/mL group, catalpol-24 g/mL group, catalpol-48 g/mL group, catalpol − 48   g / mL + vector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Catalpol, an iridoid glucoside contained richly in the roots of the small flowering plant species Rehmannia glutinosa Libosch, has been revealed to have antioxidant, anti-inflammation, and anti-apoptosis properties [ 165 ]. Based on some results, treatment of lung cancer cells with catalpol remarkably reduce the protein levels of Nrf2 and HO-1 compared with the control group [ 166 ].…”
Section: Nrf2/ho-1 Axis Modulating By Natural Antioxidants In Lung Ca...mentioning
confidence: 99%
“…Catalpol, an iridoid glucoside contained richly in the roots of the small flowering plant species Rehmannia glutinosa Libosch, has been revealed to have antioxidant, anti-inflammation, and anti-apoptosis properties [ 165 ]. Based on some results, treatment of lung cancer cells with catalpol remarkably reduce the protein levels of Nrf2 and HO-1 compared with the control group [ 166 ].…”
Section: Nrf2/ho-1 Axis Modulating By Natural Antioxidants In Lung Ca...mentioning
confidence: 99%
“…Glycyrrhizin hampers the migration and invasion of lung cancer cells, an effect intricately linked to its reduction in the activity of the JAK/STAT signaling pathway ( Wu et al, 2018 ). A study by Wang et al ( Wang et al, 2022 )unveiled that catalpol, extracted from Radix Rehmanniae, hinders the Nrf2/ARE signaling pathway, leading to a substantial decrease in the proliferation and migration abilities of lung cancer cells. The primary mechanism behind the anti-lung cancer effect of Fritillaria extract revolves around protein phosphorylation.…”
Section: Treatment Of Lung Cancer With Traditional Chinese Medicine E...mentioning
confidence: 99%
“…Ligusticum wallichii (Ligustrazine) blocking the Wnt/β-catenin signaling pathway Dong et al (2020) Ophiopogon japonicus extract inhibiting the PI3K/Akt/mTOR signaling pathway Chen et al (2017) Licorice (Glycyrrhizin) inhibiting the JAK/STAT signaling pathway Wu et al (2018)Radix Rehmanniae (catalpol) inhibiting the Nrf2/ARE signaling pathwayWang et al (2022) …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%